Determining larval settlement, post-settlement and weaning substrates and regimes for the sea urchin Tripneustes gratilla in intensive aquaculture - Bennett, Michael Andrew (Department of Biological Sciences, 2023)
Sea urchins gonads are a highly valued and priced seafood. Demand is stable and unlikely to decline in the future. Successful echinoculture is limited by the ability to produce large enough quantities of viable larvae and/or juveniles economically and efficiently due to a bottleneck in production during the settlement and post-settlement phases. In this study, larval settlement, post-settlement growth, and weaning regimes were investigated in the collector urchin, Tripneustes gratilla. Two cohorts of urchins were spawned for two separate growth trials. Growth trials assessed settlement, post-settlement growth, and the timing of weaning onto macroalgae (Ulva lacinulata). Experimental substrates tested include: Ulvella lens, fresh Ulva, dried Ulva and alginate, dried Ulva and agar, Nitzschia sp. (undescribed diatom), dried Isochrysis galbana and alginate, probiotic Vibrio midae SY9 and alginate, V. midae SY9 and Ulva extract F9 and alginate, an ethanol-alcohol and alginate control, and a null-alginate control (replicates=4, n=35 individuals). The highest average settlement success was achieved on fresh Ulva (67.14% ± 8.45) followed by Ulvella lens (55.71% ± 12.26) and then Nitzschia sp. (40.71% ± 5.88). These treatments were significantly different from all the other treatments (p< 0.05) but not from each other (p< 0.05). U. lens facilitated the greatest significant change in test diameter in T. gratilla post-settlement (difference of 3013µm over 4 weeks) and maintained high survival over this time (61.43% ± 10.47). Weaning was successful at 4 weeks post-settlement but was accompanied by a lag-phase in observable growth that was not observed when urchins were subjected to delayed weaning (three weeks later). Survival of urchins with delayed weaning was significantly greater than that of juveniles subjected to early weaning (p< 0.05): 100.00% compared to 92.50%; and achieving a significantly greater size: ̴̴ 1.5 mm difference in test diameter over 6 weeks. Results suggest that U. lens can induce settlement while maintaining high survival. When inducing settlement using U. lens, fresh Ulva should be placed in the same tank to facilitate increased settlement, U. lens facilitating post-settlement growth thereafter. The timing of weaning is important in facilitating optimal growth.